Decentralization reforms in Mozambique: The role of institutions in the definition of results - Salvador Forquilha (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
With the introduction of the economic reforms in the late 1980s, the opening up of the political arena and the end of the civil war in the early 1990s, the decentralization process began in Mozambique. Different research developed in recent years shows that, as is the case in other countries in sub-Saharan Africa, the impact of the decentralization reforms on the promotion of local development and the strengthening of democracy in Mozambique is modest. How can this modest impact be explained? Based on three important reforms in the decentralization process in Mozambique, namely the '7 million', municipalization and decentralized provincial governance, this article seeks to answer this question by analysing how different aspects of the institutions affect the results of the reforms. The main argument in the article underlines the idea according to which the results of the decentralization reforms in Mozambique are constrained by the nature and by the operation mechanisms of the political system. Of these institutional factors/constraints, state capacity and independence from private interests, particularly political groups, stand out in the three reforms analysed throughout this article. In this context, the reforms develop according to group interests, particularly party political interests, which capture the state and use the reforms as a mechanism for maintaining and bolstering political power. In this sense, rather than being a means of improving the provision of public services and strengthening democracy, decentralization works more as an instrument for reinforcing state control and pandering to the elite. This is probably the biggest challenge decentralization is facing in Mozambique, therefore making it a fundamental issue to be taken into account in any reform in this area, within the context of strengthening democracy and promoting local development.
Keywords: 330; decentralization; decentralized governance; institutions; Mozambique; municipalization